Hagia Sophia dan Kebangkitan Politik Islam di Turki? (State Islamic Institute of Kudus (IAIN Kudus), 2020)
Hagia Sophia and the rise of Islamic politics in Turkey. Erdogan’s decision to take over Hagia Sophia as a mosque has received any responses from various parties both those who supported and critized it, from the government officials to the general public. Some of Muslim-majority countries generally support the Turkish government policy. However, domestically, the debate over this decision devide Turkish people into religious and secular parties. This paper aims to identifies why the shifted of Hagia Sophia as a mosque has become a monumental event and how its impact toward the growing of Islamic movements in Turkey.